The Role of the Ministry of Youth in Protection Jordanian Youth from Extremist Ideology, from the perspective of students of the University of Jordan - Khawaj, Hasan Mamdouh (Journal of Educational and Psychological Sciences, 2021)
This study aimed at identifying the role of the Ministry of Youth in protecting Jordanian youth from extremist ideology from the perspective of the University of Jordan students. The researcher used, as a tool for the study, the descriptive survey- analytical approach, and the questionnaire, which consisted of (20) paragraphs distributed over 4 fields; The study sample consisted of (856) individuals from the University of Jordan students, (496) males and (360) females, and the results showed that the overall tool obtained a total average of (3.20) out of (5), meaning that the ministry’s role achieved a (medium) level at the level of fields; The social domain got the highest average (3.36), followed by the security domain with an average of (3.18), then the religious domain with an average of (3.14), and finally the intellectual domain with an average of (3.11), all with a rating of (medium), and the results did not show statistically significant differences at the level (α≤ 0.05) among the sample estimates for the role of the Ministry of Youth in protecting Jordanian youth from extremist ideology that is attributed to the gender variable in the intellectual and security field, while significant differences were found in the social and religious fields, in favor of male students. The results did not show differences according to the academic level variable in the social field, while they showed significant differences in the (religious, security, and intellectual) fields and in favor of doctoral students compared to other academic levels.In light of the results of the study, the researcher recommended the necessity of strengthening the role of the Ministry of Youth in protecting young people from extremist ideology and networking between the Ministry of Youth, the government and the private institutions and organizations to develop an integrated system to protect young people from extremist ideology, and building the capacities of workers to protect young people from extremist ideology. He also suggested preparing a similar study that includes all university students; at the level of the Hashemite Kingdom of Jordan.
Keywords: Extremist thought; the role of the Ministry of Youth; youth protection; a viewpoint; University of Jordan students